Konsep Plesetan sebagai "Visual Pun" Lokal pada Media Promosi Luar Ruang Usaha Kuliner Masyarakat Yogyakarta - Sudjadi Tjipto; Imam Santosa; Naomi Haswanto (Wimba : Jurnal Komunikasi Visual, 2012)
In Yogyakarta form of humor in communicating called the (language) plesetan. Interesting phenomenon occurs when plesetan that was originally a lingua franca is then used as an advertising concept culinary business. Actorsâ culinary business with the help of graphic design utilizing digital printing technology in producing a media campaign with the concept of a plesetan. The research methods used in this study play purely descriptive phenomenology methodology pioneered by Edmund Husserl. Data was collected through field observations by documenting the work of the media campaign culinary business in Yogyakarta and surrounding areas. Interviews were conducted to reveal the informant lived experience of a first person perspective. With this method are expected to be found in the explanation of the concept of Javanese plesetan culture. Then also sought various forms of plesetan in the media and the promotion of outdoor culinary business in Yogyakarta. From the initial observations that have been made assumed plesetan performed by the high level of culinary competition. Found an interesting proof of the theory that good plesetan will continue spoofed.